COPPER OXIDE NANOPARTICLES SYNTHESIS USING AERVA JAVANICA AND THEIR ANTIMICROBIAL ACTIVITIES - G. Afzal; A. Jamal; S. Kiran; G. Mustafa; T. Mehmood; F. Ahmad; S. Saeed; A. Ali; N. Naz; S. S. Zehra; S. Khalil; S. Dawood (Journal of Animal and Plant Sciences, 2022)
In the field of nanomedicine, copper oxide nanoparticles (CuO NPs) are remarkable and foremost transition metal oxides having engrossing features. Their green synthesis is getting popularity as future antimicrobials due to cost effective, eco-friendly and simplicity. In this study, CuO NPs were synthesized from Aerva javanica (kapok bush or desert cotton) leaf extract which is well known for its medicinal properties. Antimicrobial potential of A. javanica synthesized CuO NPs was assessed against multi drug resistant bacterial and fungal strains. CuO NPs synthesised in this study were characterized using Uv-Visible, X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDXS). These fabricated CuO NPs were studied for their antimicrobial activity using disc diffusion method against multi drug resistant bacterial and fungal strains. Uv-Vis with absorbance band of 255nm confirmed the CuO NPs. XRD pattern distinctive structural peaks that confirmed the typical monoclinic CuO NPs structure. The average measured diameter of CuO NPs by XRD was 5.5 nm. FT-IR spectrum 1378 cm-1-1524 cm-1 displayed CuO vibrations. SEM studies revealed the spherical and agglomerated synthesized CuO nanoparticles. EDXS showed strong peak of copper and oxygen and low peak of carbon elements due to capping of biomolecules. CuO NPs exhibited significant (p<0.005) antimicrobial activity against resistant bacterial strains. However, the significant inhibitory effect was reported in gram negative as compared to gram positive bacterial strain. CuO NPs showed significant (p<0.005) antifungal activity. However, Aspergillus exhibited higher sensitivity as compared to Candida. Based upon our results, it can be anticipated that biologically synthesized CuO NPs can play role as promising therapeutic agents in nanomedicine field.
Keywords: Cuo NPs; Uv-Vis; XRD; FT-IR; Candida albicans; Aspergillus niger; Staphylococcus aureus; Pseudomonas aeruginosa